2023
DOI: 10.3390/jcm12041677
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Preserflo MicroShunt Intraluminal Stenting for Hypotony Prevention in Highly Myopic Patients: A Comparative Study

Abstract: Transient hypotony is the most common early complication after Preserflo MicroShunt (PMS) implantation. High myopia is a risk factor for the development of postoperative hypotony-related complications; therefore, it is advisable that PMS implantation in patients should be performed while employing hypotony preventive measures. The aim of this study is to compare the frequency of postoperative hypotony and hypotony-related complications in high-risk myopic patients after PMS implantation with and without intral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
2
6
0
1
Order By: Relevance
“…(28.57 %) was comparable to other studies on the PM (11.1 to 39 % of the eyes) [15]. It suggests that the risk of postoperative hypotony with the PM in highly myopic patients and non-highly myopic patients could be the same.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…(28.57 %) was comparable to other studies on the PM (11.1 to 39 % of the eyes) [15]. It suggests that the risk of postoperative hypotony with the PM in highly myopic patients and non-highly myopic patients could be the same.…”
Section: Discussionsupporting
confidence: 84%
“…During the follow-up of our patient, Lupardi et al showed an efficacity in the non-stented group and intraluminal stented group on IOP reduction (46.70 and 49.01%) with 80.95 and 76.19% complete success (IOP ≤ 18 mmHg or ≥ 30% IOP decrease without medications) at the 6-month visit. It is also interesting that the rate of hypotony in the non-stented group (28.57%) was comparable to other studies on the PM (11.1 to 39% of the eyes) 15 . It suggests that the risk of postoperative hypotony with the PM in highly myopic patients and non-highly myopic patients could be the same.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations